mTORC1-Mediated Angiogenesis is Required for the Development of Rosacea - Peng, Qinqin; Sha, Ke; Liu, Yingzi; Chen, Mengting; Xu, San; Xie, Hongfu; Deng, Zhili; Li, Ji (Frontiers in Cell and Developmental Biology, 2021)
Although multiple evidences suggest that angiogenesis is associated with the pathophysiology of rosacea, its role is still in debate. Here, we showed that angiogenesis was enhanced in skin lesions of both rosacea patients and LL37-induced rosacea-like mice. Inhibition of angiogenesis alleviated LL37-induced rosacea-like features in mice. Mechanistically, we showed that mTORC1 was activated in the endothelial cells of the lesional skin from rosacea patients and LL37-induced rosacea-like mouse model. Inhibition of mTORC1 decreased angiogenesis and blocked the development of rosacea in mice. On the contrary, hyperactivation of mTORC1 increased angiogenesis and exacerbated rosacea-like phenotypes. Our in vitro results further demonstrated that inhibition of mTORC1 signaling significantly declined LL37-induced tube formation of human endothelial cells. Taken together, our findings revealed that mTORC1-mediated angiogenesis responding to LL37 might be essential for the development of rosacea and targeting angiogenesis might be a novel potential therapy.